Biomarker Composition of Some Oil Seeps from West Sulawesi, Indonesia - Sutadiwiria, Yarra; Hamdani, Ahmad Helman; Sendjaja, Yoga Andriana; Haryanto, Iyan; Yeftamikha, Yeftamikha (Indonesian Journal on Geoscience, 2018)
DOI: 10.17014/ijog.5.3.211-220A suite of oil seep samples collected from the Lariang and Karama Basins, West Sulawesi, Indonesia, have been analyzed using GC and GCMS techniques. Their biomarker compositions have been used to reveal the likely source rock that produces oil. These oil seep samples contain a range in both the concentration of hydrocarbons present and certain level of biodegradation experienced. All sterane m/z 217 data display a familiar pattern of steranes with carbon numbers from 27 to 29 together with pregnane and homo-pregnanes, including rearranged steranes. Triterpane (m/z 191) data show a moderate content of tricyclic terpanes (Tri/C30H), medium to high ratio of norhopane/hopane (C29/C30), and medium to high abundant land plan marker such as resin bicadinanes(Bic/C30H) and oleananes (Ol/C30H). The presence of high abundant oleananes in these samples has been interpreted as the evidence for a marine influence during early diagenesis that may occur by marine or via re-deposition of peat organics in marine sediments. Hence, these results state that the organic matter facies for their source rock oil seep samples from the West Sulawesi region are detected as mixed between allochthonous macerals from typical terrestrial higher plants transported into the basin from distal swamps and soils and some marine organic matter.